2012
DOI: 10.1177/1756283x12437358
|View full text |Cite
|
Sign up to set email alerts
|

Overutilization of proton-pump inhibitors: what the clinician needs to know

Abstract: Proton-pump inhibitors (PPIs) remain the leading evidence-based therapy for upper gastrointestinal disorders, including gastroesophageal reflux disease, dyspepsia, and peptic ulcer disease. The effectiveness of PPIs has led to overutilization in multiple treatment arenas, exposing patients to an increasing number of potential risks. The overutilization of PPIs in ambulatory care settings is often a result of failure to re-evaluate the need for continuation of therapy, or insufficient use of on-demand and step-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
206
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(239 citation statements)
references
References 84 publications
(121 reference statements)
4
206
0
8
Order By: Relevance
“…Although many confounders were included, residual confounding may exist. Other studies have suggested some potential confounding variables that were not measured in the current study, including vitamin B12 deficiency, community acquired pneumonia, clostridium difficile, Helicobacter pylori [3,41] and celiac disease [42]. The large population based case-control study by Lam et al [41] on PPI use and vitamin B12 deficiency, showed a significant association between previous and current PPI use and the existence of a vitamin B12 deficiency.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Although many confounders were included, residual confounding may exist. Other studies have suggested some potential confounding variables that were not measured in the current study, including vitamin B12 deficiency, community acquired pneumonia, clostridium difficile, Helicobacter pylori [3,41] and celiac disease [42]. The large population based case-control study by Lam et al [41] on PPI use and vitamin B12 deficiency, showed a significant association between previous and current PPI use and the existence of a vitamin B12 deficiency.…”
Section: Discussionmentioning
confidence: 54%
“…These findings highlight the need for a more careful approach to PPI prescription, as treating resulting osteoporosis may not be easy. As PPI treatment is often continued without verification or repeated confirmation of indication and/or lowest dose prescription, treatment on demand and step-down therapy should be considered more often [3,49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the risk factors associated with the prolong use of PPIs, it is important that patients follow-up with their physicians for reevaluation. Studies have revealed that overutilization of PPIs happens quite frequently and occurs primarily in patients requiring long-term treatment [7].…”
Section: Introductionmentioning
confidence: 99%